Redescription of the highly endangered species Scutellastra mexicana (Broderip & G.B. Sowerby I, 1829) (Mollusca, Gastropoda). Issue 15 (17th April 2020) - Espinosa, F.; Carballo, J. L.; Bautista-Guerrero, E.; Yáñez, B.; García-Gómez, J. C.; Michel-Morfín, J. E.
ABSTRACT: Scutellastra mexicana: (Broderip & G.B. Sowerby I, 1829) is the largest limpet in the world and a highly endangered species from the Eastern Pacific that has faced a road to extinction during the last decades. Despite the relevance of S. mexicana, basic data, such as those relevant to its biology and ecology, have not been studied. In addition, previous descriptions of the species were focused only on shell morphology with few details. Very different morphologies between small and large-sized specimens were reported previously, in accordance with the trait already described for specialist species about adult/juvenile differentiation. Here, a new set of data about shell description, soft tissue, radula and genetics are reported in order to make a re-description of the species. Both type of specimens (small and large-sized) genetically belong to S. mexicana with clear traits on shell morphology and soft tissue parts that allow an accurate identification. Considering that small morphology can be found in reproductive specimens, such differences would be caused by shell growth and the erosion provoked by the extreme wave-exposed environment where the species lives. Analyses of the independent COI and 16S datasets revealed that none of the sequences of S. mexicana had any close relationship with other members of Scutellastra ; thus, S. mexicana formed an independent and monophyletic clade relative to the other clades.